Relationship of Insecticidal Activity and Resistance to Proteolysis of Two Glucose/ Mannose Plant Lectins - Freitas, Cleverson Diniz; Ramos, Marcio Viana; Souza, Diego Pereira; Marinho-Filho, Jose Delano Barreto; Teixeira, Fabiano Moura; Oliveira, Jefferson Soares (Comunicata Scientiae, 2011)
Purified seed lectins from the legumes Canavalia brasiliensis (ConBr) and Cratylia floribunda (CFL) were tested for insecticidal activity against Callosobruchus maculatus (Coleoptera: Bruchidae) and Dysdercus peruvianus (Hemiptera: Pyrrhocoridae). ConBr and CFL caused negative effects on larvae of C. maculatus at levels of 1% and 2% (w/w). Time of development of C. maculatus insects, grown in artificial seeds containing both lectins, was not significantly altered, but the emergence was slightly diminished. Both lectins were resisted to proteolysis by gut proteases of C. maculatus larvae. Artificial diets containing 1% and 2% of ConBr or CFL caused no effect on weight and survival of D. peruvianus nymphs. Gut proteases of D. peruvianus were able to breakdown ConBr and CFL after 2 hours of incubation. The ability of insects to digest the proteins was correlated directly with the deleterious effect observed.